Clinical spectrum of severe chronic central serous chorioretinopathy and outcome of photodynamic therapy - Mohabati D; van Dijk EHC; van Rijssen TJ; de Jong EK; Breukink MB; Martinez-Ciriano JP; Dijkman G; Hoyng CB; Fauser S; Yzer S; Boon CJF (Clinical Ophthalmology, 2018)
Danial Mohabati,1,2 Elon HC van Dijk,1 Thomas J van Rijssen,1 Eiko K de Jong,3 Myrte B Breukink,3 Jose P Martinez-Ciriano,4 Greet Dijkman,1 Carel B Hoyng,3 Sascha Fauser,5 Suzanne Yzer,4 Camiel JF Boon1,6 1Department of Ophthalmology, Leiden University Medical Center, Leiden, the Netherlands; 2Department of Ophthalmology, Rotterdam Ophthalmic Institute, Rotterdam, the Netherlands; 3Department of Ophthalmology, Donders Institute for Brain, Cognition and Behaviour, Radboud University Medical Center, Nijmegen, the Netherlands; 4Department of Ophthalmology, The Rotterdam Eye Hospital, Rotterdam, the Netherlands; 5Department of Ophthalmology, University Hospital of Cologne, Cologne, Germany; 6Department of Ophthalmology, Academic Medical Center, University of Amsterdam, Amsterdam, the Netherlands Purpose: To describe a spectrum of severe chronic central serous chorioretinopathy (cCSC) cases and their response to photodynamic therapy (PDT).Patients and methods: A total of 66 patients (81 eyes) with active severe cCSC were studied, and their response to PDT was compared with a control group consisting of 35 active cCSCs (37 eyes) that did not display characteristics of severity. Best-corrected visual acuity (BCVA) and complete resolution of subretinal fluid (SRF) were considered as main outcome measures.Results: In severe cCSC cases, we found cumulative areas of diffuse atrophic retinal pigment epithelium alterations in 48 eyes (59%), multiple “hot spots” of leakage in 36 eyes (44%), posterior cystoid retinal degeneration in 25 eyes (31%), and 13 eyes (16%) had a diffuse leakage on fluorescein angiography. After PDT treatment, BCVA increased in both groups, from 66 to 72 Early Treatment of Diabetic Retinopathy Study (ETDRS) letters in the case group (P<0.001), and from 78 to 82 ETDRS letters in the control group (P<0.001). SRF had resolved completely in 87% of severe cCSC cases and 95% of controls at final follow-up visit.Conclusion: A spectrum of severe cCSC exists, and PDT seems to be an effective treatment in both severe cCSC and nonsevere cCSC in terms of resolution of SRF. Final BCVA shows a significant improvement in both groups after PDT treatment. Keywords: chronic central serous chorioretinopathy, photodynamic therapy, posterior cystoid retinal degeneration, severe phenotype, therapeutic outcome